(untitled) (Journal of the College of Basic Education, 2023)
A genus of Salmonella was isolation and identification from 40 stool samples of patients at different hospitals in Baghdad, during the period between June 2001 and July 2002. The following serotypes were isolated: - S.typhimurium (69%), S.enteritidis (10%), S.typhi (8%) and (13%) of other Salmonella species. All isolates were screened for their resistance to amoxicillin, ampicillin, chloramphenicol, co-trimexazole, cephalexin, cefotaxaime and ciprofloxacin, using disc diffusion method. Salmonellae typhimurium isolates (80%) were multidrug resistance (MDR) for six antimicrobial agents. Screening of plasmid content revealed that the presence of single mega plasmid was found in 72.7% of multidrug resistance Salmonella isolates and presence of small plasmid in all tested isolates was detected. High frequency molecular weight was observed in the range between 2.1-2.93kb (1.33-1.86Md), in Salmonella isolates.